İslamiyet Öncesi Eski Türk İnanışları veya Mitolojisi ile Antik Dönem (Yunan veya Roma) Mitolojisinin Karşılıklı Olarak Değerlendirilmesi - Uzun Aydın, Derya (Muş Alparslan Üniversitesi, 2019)
Mythology can also be called as “Science of Legends”. The importance ofthe theme of mythology for ancient Greek and Roman which was based on Europeand its origin is an is disputable truth. In this context, the fact that howimportant were the mythological theme stories Old Turks will be relieved. InTurkish mythology, ancestor cult, god faith especially Shamanism or Buddhism, “balbals”, nomadic life cult, and of course animal style are the first topics thatcome to mind concerning Turkish art and mythology. The Greek or Romanmythology, which originated in the European mythology, attracts attention with itsmythology, which consists of the universe and the beginning of the world, the existenceof man, the phenomena that exist in nature and the great people of Olympos, God, Goddess, Half Gods or mythological-mythical creatures. The existence ofcult beliefs such as birth, life, universe, nature will be seen in the weave ofevents.

Mitoloji, “Efsaneler Bilimi” olarak da adlandırılabilir. Mitolojitemasının Avrupa ve kökeninin dayandığı Antik Yunan veya Roma için ne kadarönemli olduğu tartışılmaz bir gerçektir. Bu bağlamda, Eski Türklerde mitolojik tema öykülerinin de ne kadardeğerli olduğu gerçeği ortaya çıkacaktır. Türk mitolojisinde, ata kültü, tanrıinancı özellikle Şamanizm veya Budizm, balballar, anıtlar, göçebe yaşam kültüve elbette hayvan üslubu Türk sanatı ve mitolojisinde akla ilk gelen konularolmaktadır. Avrupa Mitolojisine kaynaklık eden Yunan veya Roma mitolojisi deevren ve dünyanın başlangıcı, insanın var oluşu, doğada var olan olgular veOlympos’lu büyükler yani Tanrı, Tanrıça, Yarı Tanrılar veya mitolojik-efsaneviyaratıklardan oluşan zengin mitolojisi ile dikkat çekmektedir. Olaylarörgüsünde doğma, yaşam, evren, doğa gibi kült inanışların varlığı görülecektir.
Mutual Evaluation of Ancient Turkish Beliefs or Mythology before Islam and the Ancient Period (Greek or Roman) Mythology
anemon
Keywords: Mythology; Middle Asia; Old Turks; Antiquity; Mitoloji; Orta Asya; Eski Türkler; Antik Dönem